Antibiotic Resistance in Microbes: History, Mechanisms, Therapeutic Approaches, and Strategies for Mitigation - Masirah Shaikh; Bhagyashri Pawar; Shruti Chougule; Raju Rathod (International Journal of Antibiotics, 2025)
The global emergence of clinically significant antibiotic resistance is increasingly linked to the environment. Antimicrobials, metals, and biocides are just a few of the substances that are released into the environment through paths that are regulated by environmental regulators. Consequently, environmental regulators ought to be heavily involved in developing national and international antimicrobial resistance (AMR) measures. Antimicrobial compounds from pharmaceutical waste, agricultural runoff, and wastewater discharge contribute to the spread of resistance genes in natural ecosystems. However, many AMR action plans lack strategies addressing environmental reservoirs due to limited understanding of AMR pathways and pollutant-microbe interactions. Environmental regulators, such as England’s Environment Agency, can help by monitoring pollutants, enforcing antimicrobial discharge regulations, and collaborating with public health and agricultural sectors. Their role should expand beyond pollution control to include research, surveillance, and risk assessment. Strengthening their involvement will enhance AMR action plans, leading to more effective global mitigation strategies. The purpose of this study is to illustrate the issue of AMR in the environment from the viewpoint of an environmental regulator by utilizing the Environment Agency, which is the regulatory body in England, as an example from which global comparisons can be made. There are some suggested thought experiments.
Keywords: Biocide; antibiotics; antimicrobial resistance; genes; metals; plasmid